Extraction and Characterisation of Natural Fibres from Imperata cylindrica: Morphological, Microstructural, Thermal, and Kinetic Properties - Bemgba B. Nyakuma; Olagoke Oladokun; Ezekiel B. Ogunbode; Segun A. Akinyemi; Syieluing Wong; Jamila B. Ali; Hasan M. Faizal; Tuan Amran T Abdullah (Journal of Natural Fibers, 2022)
In this study, natural fibers were extracted from Imperata cylindrica (ICY) by mechanical fractionation followed by characterization. The morphological, microstructural, and thermal properties of ICY fibers were examined by scanning electron microscopy (SEM), energy-dispersive X-ray, and thermal gravimetric analysis (TGA). Kinetic analysis was examined through Flynn Wall Ozawa (FWO) and Kissinger Akahira Sunose (KAS) models. Results showed that mechanical fractionation successfully extracted natural fibers from ICY. SEM analyses revealed a compact surface structure interrupted by contours and protrusions due to disoriented fractionation of the fibers. Thermal analysis revealed significant mass loss (72.94–77.03%), whereas the TG/DTG plots shifted correspondingly due to multiple heating rates (10–30°C/min) and thermal lag during TGA from 30 to 800°C. Likewise, the onset, midpoint, offset, drying, and devolatilization peak temperatures increased at higher heating rates. Tons increased from 257.99–269.25°C, whereas Tmid was 313.57–319.17°C, Toff was 363.70–376.58°C. The OFW and KAS kinetic models revealed activation energy (Ea) and frequency factor (ko) ranged from 38.09 to 514.33 kJ mol−1 and 1.65 × 1002 to 1.24 × 1048 min−1, respectively, for conversions α = 0.05 to 0.95, which indicate ICY fibers are thermally stable and suitable for utilization as bio-composite reinforcement.